Resource block filtered-OFDM as a multi-carrier transmission scheme for 5G. (November 2018) - Zhao, Yingxin; Hao, Xiuying; Liu, Zhiyang; Wu, Hong; Ding, Shuxue
Highlights: A new multi-carrier technique for future wireless communications is proposed. The proposed technique has a better performance than previous systems. The new system has strong practical significance and potential application. Abstract: The fifth generation of mobile communications, which has higher requirements for data rate and spectral efficiency, will be a key technology for future wireless communication systems. Therefore, based on the current spectral division, the use of idle spectra of low-frequency bands is needed to address 5G mobile scenarios. The side lobe in frequency division multiplexing (OFDM), which is widely adopted in 4G, is so high that it produces adjacent channel interference. The addition a cyclic prefix is necessary to resolve such an interference problem; however, this leads to spectral efficiency degradation. Therefore, this study presents a new multi-carrier transmission technique for future wireless communication systems. Intuited by the filter bank based multi-carrier (FBMC) and the universal-filtered multi-carrier (UFMC), we proposed band resource block filtered orthogonal frequency division multiplexing (RB F-OFDM). RB F-OFDM retains the advantages of OFDM; moreover, its sideband has rapid attenuation, its energy is more concentrated, and it can avoid inter-carrier interference (ICI). When adjacent channel interference exists, the performance of RB F-OFDM is better than that of OFDM and UFMC.